Pengaruh Kebiasaan Membaca di Rumah terhadap Kemampuan Membaca Pemahaman Siswa SD : Sebuah Kajian Literatur - Diva Rizkia Fadillah; Kharisma, Inggria; Nur Azmi Alwi (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
The purpose of this study was to analyze the influence of reading habits at home on elementary school students' reading comprehension skills using a literature review approach methodology (library research). Reading comprehension skills are a significant factor in learning activities, and early reading habits in the family environment are considered to have a great influence in improving them. Based on the results of studies from various literature sources, it was found that students who regularly carry out reading activities at home tend to have better levels of reading comprehension, more vocabulary, and higher reading interest compared to students who do not have these habits. Many influencing factors such as parental involvement, variety and availability of reading materials, and special time for reading at home, foster this influence. Thus, improving reading culture at home is an important strategy to support the literacy success of elementary school students.